Detection of Intranasally Delivered Bone Marrow-Derived Mesenchymal Stromal Cells in the Lesioned Mouse Brain: A Cautionary Report - Elena H. Chartoff; Diane Damez-Werno; Kai C. Sonntag; Linda Hassinger; Daniel E. Kaufmann; Jesse Peterson; Donna McPhie; Anne M. Cataldo; Bruce M. Cohen (Stem Cells International)
Bone marrow-derived mesenchymal stromal cells (MSCs) hold promise for autologous treatment of neuropathologies. Intranasal delivery is relatively noninvasive and has recently been reported to result in transport of MSCs to the brain. However, the ability of MSCs to migrate from nasal passages to sites of neuropathology and ultimately survive has not been fully examined. In this paper, we harvested MSCs from transgenic mice expressing enhanced green fluorescent protein (cells hereafter referred to as MSC-EGFP) and delivered them intranasally to wild-type mice sustaining mechanical lesions in the striatum. Using fluorescent, colorimetric, and ultrastructural detection methods, GFP-expressing cells were undetectable in the brain from 3 hours to 2 months after MSC delivery. However, bright autofluorescence that strongly resembled emission from GFP was observed in the olfactory bulb and striatum of lesioned control and MSC-EGFP-treated mice. In a control experiment, we directly implanted MSC-EGFPs into the mouse striatum and detected robust GFP expression 1 and 7 days after implantation. These findings suggest that—under our conditions—intranasally delivered MSC-EGFPs do not survive or migrate in the brain. Furthermore, our observations highlight the necessity of including appropriate controls when working with GFP as a cellular marker.